2012
DOI: 10.1007/s12028-012-9692-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interferon-β on Neuroinflammation, Brain Injury and Neurological Outcome After Experimental Subarachnoid Hemorrhage

Abstract: In contrast to previously published findings in experimental ischemic stroke models, interferon-β has no clear efficacy to protect the brain after SAH. In line with recent highlighting of the significance of negative findings, our data currently do not recommend clinical testing of interferon-β to prevent neurological damage in SAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The delivery of adiponectin (30 kDa) into the brain parenchyma has also been hampered by the presence of the BBB. Previous studies have shown that many recombinant protein drugs can be introduced to avoid the shortcomings of gene therapy for clinical applications, including neurogenin-2 (Ngn2) and interferon [91,92]. The Ngn2 protein can be regulated in the CNS simply via the delivery of recombinant Ngn2 fusion protein [91].…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…The delivery of adiponectin (30 kDa) into the brain parenchyma has also been hampered by the presence of the BBB. Previous studies have shown that many recombinant protein drugs can be introduced to avoid the shortcomings of gene therapy for clinical applications, including neurogenin-2 (Ngn2) and interferon [91,92]. The Ngn2 protein can be regulated in the CNS simply via the delivery of recombinant Ngn2 fusion protein [91].…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Both intra-and extravascular leukocytes will contribute to the inflammatory state of the brain and will reflect recruitment and influx of immune cells towards the site of injury. Cerebral inflammation detected at 48 hours after SAH seems to persist since Tiebosch et al (2013) showed an increased MPO expression even 7 days after SAH using the same endovascular puncture model [28]. Only a few reports about the expression of anti-inflammatory cytokines after SAH are available [25], [38][40].…”
Section: Discussionmentioning
confidence: 99%
“…Most animals were part of a drug treatment study in which animals received subcutaneous injection of either 0.022 mg/kg interferon-β (n = 16) or vehicle (n = 14) [9]. That study revealed no differences in lesion size, neurological status and mortality rate between treatment groups, and therefore, data were pooled.…”
Section: Methodsmentioning
confidence: 99%